Sejarah Yahudi dan Uzair Dalam Al-Qur’an: (Kajian Surat at-Taubah ayat 30) - Syamun, Fitriyah (TARIKHUNA: JURNAL SEJARAH PERADABAN ISLAM, 2025)
Abstract There were several names of person which mentioned in the Qur'an, the holy book of Islam, being debated about the status of a prophet or a pious person. Moreover, Qur'an described not only 25 names of prophet should be believed but also prophet stories beyond that names. One of the story was about Uzair. The name of Uzair was mentioned in the Qur'an, juxtaposed Jews claimed Uzair as Allah son. On the other hand, people ignorance about Uzair because of the name just once noticed in the Qur'an, paragraph 30 of At-Taubah. Therefore,Uzair and the relationship with Jews will be explained deeply in this writing by Library Research method. From this research, found that Uzair was special person and had big effectness for Jews. Furthermore, famous people stated that Uzair was a prophet. However, some of the Israelites who had bad manners and morals experienced regeneration until the time of Uzair. The story of Uzair has the miracle of being able to rewrite the book of the Torah which had previously been lost because it was burned by an unjust king, causing excessive worship of their cleric. The rewriting of the Torah should have made the people of Israel more likely to practice its contents well, but in fact the opposite happened. Keywords: Uzair, Jews, Qur'an, Israel